Pengaruh Penggunaan Model Pembelajaran Kooperatif Tipe Two Stay-Two Stray Terhadap Kemampuan Komunikasi Matematis dan Kemampuan Pemecahan Masalah Matematika Kelas VIII SMPN 6 Moncongloe Kab. Maros - Harsuci Ramadhani; Mardhiah; Suharti; Ruslimin; Satriawati (Department of Mathematics Education, 2023)
The purpose of this study was to determine the effect of using the two stay-two stray type cooperative learning model on mathematical communication skills and mathematical problem solving skills of class VIII students of SMPN 6 Moncongloe. The research used was Quasi Experiment with Non Equivalent Control Group Design research design. The study population was all VIII grade SMPN 6 Moncongloe totaling 128 people with samples in both classes totaling 32 students each. This research instrument is a test of mathematical communication skills and mathematical problem solving skills in the form of pretest and posttest tests. The analysis technique used is descriptive statistics and inferential statistics using multivariate mean difference test. The results showed: (1) students' mathematical communication skills after the use of the two stay-two stray learning model are in the high category with a percentage of 56.25%. (2) students' mathematical communication ability using two stay-two stray type cooperative learning model has a significant effect based on the output of the test of beetween-subjects effect, namely students' mathematical communication ability has a significance of 0.0001 so that the value is less than 0.05 (0.0001<0.05). (3) mathematical problem solving ability using two stay-two stray type cooperative learning model has a significant effect based on the output of the test of beetween-subjects effect, namely students' mathematical problem solving has a significance of 0.0001 so that the value is less than 0.05 (0.0001<0.05). (4) there is a significant effect of two stay-two stray type cooperative learning model on students' mathematical communication ability and mathematical problem solving ability as evidenced by the multivariate test output in the effect section of the class both according to Pillai's Trace, Wilks' Lambda, Hotelling's Trace, and Roy's Largest Root all significance values are 0.0001 so that it is less than 0.05 (0.0001<0.05).